2011
DOI: 10.1258/ijsa.2010.010355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of a social networking site in sexual health care

Abstract: The Myspace project was launched in 2008 to develop a novel approach to engage with younger sexual health service users. The aim was to use a social networking site as a patient forum, to gain feedback on how to improve services and to make sexual health information accessible to a larger audience, many of whom might not be current service users and thereby to encourage attendances from more 'hard to reach' groups. In this report, we explore the effectiveness and specific challenges of the project and in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…The consensus among the groups was that the approach to providing an educational Web‐based site has the potential of reaching individuals seeking trustworthy sexual health information and potentially affecting subsequent risky sexual behaviors. These findings align with the systematic review conducted by Hedge and Donald () who found among four social networking sites including sexual health information, a significant number of participants reported the sites were useful (85%) and they would use them to seek out sexual health information (81%). In addition, Yager and O’Keefe () reported 58% of respondents increased their knowledge of STD's after viewing their Teen Sexual Health Information Facebook page.…”
Section: Discussionsupporting
confidence: 88%
“…The consensus among the groups was that the approach to providing an educational Web‐based site has the potential of reaching individuals seeking trustworthy sexual health information and potentially affecting subsequent risky sexual behaviors. These findings align with the systematic review conducted by Hedge and Donald () who found among four social networking sites including sexual health information, a significant number of participants reported the sites were useful (85%) and they would use them to seek out sexual health information (81%). In addition, Yager and O’Keefe () reported 58% of respondents increased their knowledge of STD's after viewing their Teen Sexual Health Information Facebook page.…”
Section: Discussionsupporting
confidence: 88%
“…The result of the survey for the Facebook page evaluation reported 58% of respondents said they learned more about sexually transmitted infections, and 50% said the information on the page was sufficient (Yager & O'Keefe, ). Hedge and Donald () developed the “Watford Sexual Health Centre” sites on four SNS (MySpace, Facebook, Bebo, and Hi5) to use as patient forums and sexual health information sources to reach larger audience. The survey evaluating the sites showed that 85% of users said the site was useful, and 81% said they would use the sites for sexual health information.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bebo is popular in the United Kingdom and Hi5 is popular in Latin America (Upbin, ). Previous studies have found that AYAs are interested in not only utilizing SNS for communicating with friends, but also for searching and obtaining health‐related information (Baptist et al, ; Hedge & Donald, ). This then may indicate the important potential of using SNS as a medium for maximizing the dissemination of health‐related information among AYAs, given their access frequency and comfort level with SNS.…”
mentioning
confidence: 99%
“…219 Other approaches to exploiting social networking opportunities include development of Facebook pages for communicating health information by health professionals 92,220 or from the clinical setting. 221 However, there was limited success of some of these initiatives in promoting the dialogues with at-risk groups. 220 Attracting young people to relevant sites may be difficult.…”
Section: Use Of Technology: Social Networking Sitesmentioning
confidence: 99%